Educational Attainment and Family Gaps in Women's Wages: Evidence from Five Industrialized Countries - Erin L. Todd (Luxembourg Income Study (LIS), 2001)
This paper employs Luxembourg Income Study data for women in five industrialized countries to answer the following questions: Do family gaps in women's wage vary across levels of education? Does educational attainment help to 'insure' a woman against child wage penalties? Cross-national analysis of 'family gaps' in women's wages provides clear evidence that wage penalties to motherhood vary significantly in magnitude across countries. Harkness and Waldfogel (1999) estimate these differentials between the wages of mothers and non-mothers for seven industrialized countries. They find that family gaps appear to be largest in Anglo-Saxon countries. The character of our research is primarily exploratory, but some basic conclusions can be drawn from our results. In Canada and the United States, we find that a high educational attainment acts as a 'shock absorber,' almost eliminating the large negative effects of children on a woman's wages; results for Germany are similar. We find these results to be robust to the inclusion of part-time workers in the sample. We conclude that educational attainment does help to offset the family gaps faced by mothers in some countries.
Keywords: 330; Fraueneinkommen; Elternzeit; Vergleich; Deutschland; Kanada; USA; Niederlande; Schweden